2021
DOI: 10.1101/2021.05.30.446358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM Structure of the Photosynthetic LH1-RC Complex from Rhodospirillum rubrum

Abstract: We present a cryo-EM structure of the light-harvesting-reaction center (LH1-RC) core complex from purple phototrophic bacterium Rhodospirillum (Rsp.) rubrum at 2.76 Å resolution. The LH1 complex forms a closed, slightly elliptical ring structure with 16 αβ-polypeptides surrounding the RC. Our biochemical analysis detected rhodoquinone (RQ) molecules in the purified LH1-RC, and the cryo-EM density map specifically positions RQ at the QA site in the RC. The geranylgeraniol sidechains of bacteriochlorophyll (BChl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…On the other hand, the process parameters require optimization. Therefore, based on original research [9,10,28,31,32], model broths were prepared. The initial dark fermentation broth was composed of a sterile minimal medium Buffered Peptone Water (Biomaxima, Gdańsk, Poland) and lignocellulosic biomass hydrolysates, as the sole carbon source for hydrogen-generating anaerobic microorganisms; i.e., Enterobacter aerogenes ATCC 13048 [10].…”
Section: Model Photo Fermentation Broth Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the process parameters require optimization. Therefore, based on original research [9,10,28,31,32], model broths were prepared. The initial dark fermentation broth was composed of a sterile minimal medium Buffered Peptone Water (Biomaxima, Gdańsk, Poland) and lignocellulosic biomass hydrolysates, as the sole carbon source for hydrogen-generating anaerobic microorganisms; i.e., Enterobacter aerogenes ATCC 13048 [10].…”
Section: Model Photo Fermentation Broth Characterizationmentioning
confidence: 99%
“…Rhodospirillum rubrum is a frequently studied species [31], exhibiting unique nitrogenase activity, reducing both molecular nitrogen and protons to molecular hydrogen. In addition to the ability to bind carbon dioxide, it can bind nitrogen.…”
Section: Photo Fermentationmentioning
confidence: 99%
“…The compositions and architectures of RC–LH1 supercomplexes exhibit a diversity among various bacterial species 2 . Many RC–LH1 complexes occur as monomers, in which the RC is encircled by a closed LH1 ring of 16 αβ-heterodimers 7 11 , or an open LH1 ring of 15–16 αβ-polypeptides with a gap formed by specific transmembrane (TM) polypeptides 12 17 . The Rhodobacter genus is characterized by the presence of a PufX polypeptide in RC–LH1, which functions as a molecular cross brace to stabilize the monomeric core complex of Rhodobacter ( Rba .)…”
Section: Introductionmentioning
confidence: 99%
“…The recent determination of several LH1 structures using cryo-EM provides opportunities for further exploration. 19 Our previous study on LH2 demonstrated that the absorption spectrum of B850 cannot be replicated by the conventional exciton model (referred to as the monomer exciton model in this paper). 32 To address this issue, we developed a dimer exciton model, wherein the BChl a dimer was treated as a unified fragment.…”
Section: Introductionmentioning
confidence: 79%